Pemanfaatan Abu Limbah Bonggol Jagung Sebagai Bahan Substitusi Filler Untuk Campuran AC-WC - Arjuna Sanda Sau’langi; Alpius; Herman Welem Tanje (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Asphalt mixtures can be modified by adding different types of mixtures, ranging from chemical additives, natural materials, and waste waste. This study was intended to find out the characteristics of ac-wc mixtures that use corn weevil ash into filler substitution material. The method used is to perform a series of characteristic tests of corn weevil ash fillers and then the manufacture of AC-WC mixed test objects and marshall testing. From testing the characteristics of the AC-WC mixture obtained Stability 0%-100%: 1110.17kg - 1436.40kg for Flow 0%-100% : 2.41mm - 3.47mm for VIM 0%-100% : 3.21% - 4.16% for VMAs 0%-100%: 14.56% - 15.72% and for VFB 0%-100% : 73.55% - 77.96%. From the test results it can be concluded that the mixture of AC-WC with the substitution of corn weevil ash fillers that meet the general specification of bina marga 2018 is from a rate of 0%-60%.